2016
DOI: 10.1016/j.ibiod.2015.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing biomethane production from anaerobic degradation of Scenedesmus spp. biomass harvested from algae-based swine digestate treatment

Abstract: The objective of this work was to quantify biomethane from anaerobic degradation of microalgae biomass harvested from a field-scale tank reactor simulating phycoremediation of swine wastewater. The effects of nutrients starvation on microalgae chemical cellular composition changes and its influence on biomethane generation potential were also addressed. Microalgae polyculture was dominated by uncultured Scenedesmus clone BF 063 which showed a carbohydrate, protein and lipid content of 27.6 ± 3.3, 57.6 ± 0.1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 41 publications
0
13
0
2
Order By: Relevance
“…Perazzoli et al studied Scenedesmus sp. in a nutrient rich medium and estimated 57% of protein content which reduced to 23–27% when studied in nutrient free medium . Further, Scenedesmus almeriensis was grown in photoautotrophic continuous culture condition and showed 45–50% (w/w) protein in the cultured strain .…”
Section: Resultsmentioning
confidence: 99%
“…Perazzoli et al studied Scenedesmus sp. in a nutrient rich medium and estimated 57% of protein content which reduced to 23–27% when studied in nutrient free medium . Further, Scenedesmus almeriensis was grown in photoautotrophic continuous culture condition and showed 45–50% (w/w) protein in the cultured strain .…”
Section: Resultsmentioning
confidence: 99%
“…Feedstocks such as food waste or lignocellulosic biomass [2,3] have been studied as substrates for anaerobic digestion. One recent development is the use of microalgae, both as a way to recover nutrients from wastewater effluents and as a feedstock for biogas production through anaerobic 3 digestion [4] since previous studies reported that microalgae biomethanization is an economically feasible approach when their cell lipid content is lower than 40% [5]. Microalgae exhibit several characteristics that make them a promising biomass resource such as a high photosynthetic efficiency, a growth rate of 20-30 fold higher than energy crops and no direct competition with food production since microalgae could be grown on non-arable land [6].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, hydrolytic activity can be increased by carrying out the anaerobic digestion under thermophilic conditions since thermophilic microbial populations exhibits higher enzymatic activity [11], although the thermophilic process is more prone to instability than the mesophilic one due to inhibition by free ammonia [12], especially when substrates with high protein content such as 4 microalgae are digested [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the obtained values were significantly higher than that for previously reported for Chlorella pyrenoidosa (TMP = 190.41 mL g −1 VS) 35 , Spirulina platensis (SMP = 278–305 mL g −1 VS) 36 , Scenedesmus spp. (TMP = 400 mL g −1 VS) 37 , and Chlamydomonas reinhardtii (TMP = 549 mL g −1 VS) 38 . Values for both SMP and TMP at each IONPs concentration advocates enhancement in methane potential.…”
Section: Resultsmentioning
confidence: 99%